RESPON MASYARAKAT DAN DAMPAKNYA TERHADAP LINGKUNGAN DARI PROGRAM SL-PTT PADI NON HIBRIDA DI KABUPATEN HULU SUNGAI SELATAN PROVINSI KALIMANTAN SELATAN - Ria Normanita; Emmy Sri Mahreda; Siti Aminah; Fonny Rianawati (EnviroScienteae, 2015)
Increasing the productivity of rice through the approach of Sekolah Lapang Pengelolaan Tanaman Terpadu (SL-PTT) is one of the strategies that is expected to provide a greater contribution to the national rice production. Based on the results of research, the public response to the program of SL-PTT Non Hybrid Rice in Hulu Sungai Selatan was in the high category (85.71%). Factors affecting the public response to the program were the information, the field guides, the assistance component whereas those having no effects to the public response were the education, the practice, and the application of PTT. The environmental impact of the program of SLPTT Non Hybrid Rice was positive in the economic aspect, which could create welfare for farmers implementing the program. The Social aspect giving a positve impact was  through the transmission of technology adoption that could be applied to non-rice farmers who lived around the area of SL-PTT. The negative impact was the social jealousy among the people who could all not get involved in the program of SL-PTT Non Hybrid Rice.